Pedestrian dynamics on narrow pavements in high-density Hong Kong - John Zacharias (Journal of Urban Management, 2021)
Introduction: The investigation of pedestrian dynamics is important as cities continue to develop facilities for high volume foot traffic. Important insights into speed-density relationships, flow patterns, boundary effects and critical states have been derived from experimental studies. Extending these studies to real settings enables us to see how these relationships apply in settings with heterogeneous populations, complex trip purposes and undirected spatial behaviours. Hong Kong offers the opportunity to examine pedestrian dynamics in conditions of relatively dense pedestrian traffic on narrow pavements. Methods: Data were collected from a sample of 24 street environments, varying in pavement width and pedestrian flow. Individual trajectories of 356 randomly selected individuals were extracted from video records. Pedestrian speed was related to the following independent variables: pedestrian volume, pavement width, effective width and shops. Speed was also related to lateral displacement and position. Lane formation and counterflows were measured. To examine how the street environment compares with the free-flow conditions of wider, dedicated corridors, speed was measured for 356 randomly selected individuals on 7 corridors in the mass transit rail (MTR) system. Results: Displacement, effective width, number of shops and sex of the individual account collectively for 13.7% of variance in speed, while pedestrian volume was not significant. There is a slight tendency to righthand movement in bi-directional flows, with the rate of counterflow negatively related to dominant flow density. Conclusions: Walking speed on Hong Kong streets is constrained by shopping activity, obstacles and reduced spatial dimensions. Walking speed is maintained through lateral displacement, with higher speeds at the outer edge of the bounded space. People walk significantly faster in unconstrained conditions of the MTR.
Keywords: 710; Pedestrians; Pedestrian modelling; Fundamental diagram; Spatial behavior